1998
DOI: 10.1086/515342
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Matrix Metalloproteinase‐9 Activity in the Cerebrospinal Fluid of Human Immunodeficiency Virus—Infected Patients

Abstract: To determine whether matrix metalloproteinase (MMP)-9 is a potential mediator involved in the frequently detected blood-brain barrier leakage in human immunodeficiency virus (HIV)-infected patients, zymography was used to detect MMP-9 activity in cerebrospinal fluid (CSF) samples of 80 HIV-infected patients and of 10 control patients. CSF MMP-9 activity was detected in 40% of HIV-infected patients (but not in controls) and was significantly more frequent in HIV-infected patients than in those without neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 11 publications
2
50
1
Order By: Relevance
“…Importantly, our assays examine MMP-9 production on a single-cell basis, and the results were confirmed in multiple donors. These results appear to be at odds with previously published reports (9,11,36,54,59). These studies assayed biological material such as patient plasma or cerebrospinal fluid to show net increases in MMP-9 production, but could not detect whether higher production by each cell was occurring.…”
Section: Discussioncontrasting
confidence: 60%
“…Importantly, our assays examine MMP-9 production on a single-cell basis, and the results were confirmed in multiple donors. These results appear to be at odds with previously published reports (9,11,36,54,59). These studies assayed biological material such as patient plasma or cerebrospinal fluid to show net increases in MMP-9 production, but could not detect whether higher production by each cell was occurring.…”
Section: Discussioncontrasting
confidence: 60%
“…By degrading extracellular matrix proteins, such as fibronectin and collagen IV, 26 MMPs contribute to demyelinization processes in the CNS, the breaking of the blood-brain barrier, and leukocyte migration through the endothelial barrier and tissues. 25 These observations agree with the reported data in which MIP-1␣, MIP-1␤, and, to a lesser extent, RANTES promote the secretion of pro-MMP-9 by T lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…27 The presence of MMP-9 was reported in cerebrospinal fluid of HIVinfected patients. 26,28 In rapidly progressing simian immunodeficiency virus-infected monkeys, high expression of MMP-9 was correlated to both motor and cognitive deficits; in contrast, low progressors exhibited low levels of MMP-9, similar to uninfected control. 29 In addition, in vitro studies reported evidence that HIV itself, or at least the HIV Tat or Nef proteins directly promote MMP-9 secretion.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…MMP-9 is not normally present in cerebrospinal fluid (CSF), but has been detected in patients with Lyme disease (11), viral meningitis (12), human T cell lymphotrophic virus-1-associated myelopathy (13), and multiple sclerosis (14,15). MMP-9 was detected in 40% of patients with HIV infection and more commonly in cases with neurological deficit (16). CSF MMP-9 concentrations were elevated in patients with bacterial meningitis and fell during recovery (17).…”
Section: Identification Of a Matrix-degrading Phenotype In Humanmentioning
confidence: 99%